Sensitive and accurate identification of PNH clones based on ICCS/ESCCA PNH Consensus Guidelines-A summary - Illingworth, Andrea J; Marinov, Iuri; Sutherland, D Robert (International journal of laboratory hematology, 2019)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare hematopoietic stem cell disorder resulting from the somatic mutation of the X-linked phosphatidyl-inositol glycan complementation Class A (PIG-A) gene. Depending on the severity of the mutation in the PIG-A gene, there is a partial or absolute inability to make glycosylphosphatidyl-inositol (GPI)-anchored proteins including complement-defense structures such as CD55 and CD59 on RBCs and WBCs. Flow cytometric detection of PNH clones has become the gold standard and has played an increasingly important role in the diagnosis, monitoring, and clinical management of patients with PNH. Recently, a 4-part set of Consensus Guidelines have been published by flow experts in the field to address the key assay-specific considerations for the identification of PNH clones in RBC and WBC, how to report such data and a full validation document for the assays described. Below, we have summarized the most significant aspects of this International effort.
Keywords: směrnice pro lékařskou praxi jako téma; membránové proteiny; Practice Guidelines as Topic; PNH; průtoková cytometrie; aplastic anemia (AA); Membrane Proteins; Consensus; CD59; konsensus; myelodysplastic disorder (MDS); Hemoglobinuria, Paroxysmal; CD55 Antigens; Flow Cytometry; antigeny CD59; CD59 Antigens; Humans; paroxysmální hemoglobinurie; antigeny CD55; FLAER; lidé; flow cytometry